SIMULASI MONTE CARLO UNTUK MENENTUKAN DOSIS SINAR-X 6 MV PADA KETAKHOMOGENAN MEDIUM JARINGAN TUBUH - Rizani, Alfian; Setiabudi, Wahyu; Anam, Choirul (BERKALA FISIKA, 2012)
Study on dose distribution of human body at 6 MV X-ray beam has been done using Monte Carlo Simulation. This study is aimed to define dose distribution of soft tissues, lungs andbones also corrections factor due to tissue inhomogeneity.The study was conducted by Monte Carlo Simulation using EGSnrc software, i.e.BEAMnrc and DOSXYZnrc. The linear accelerator head was simulated by BEAMnrc  with SSD100 cm and field size 10 x 10 cm . The calculating of radiation dose distribution at homogen andnonhomogen phantom that have size 40 x 40 x 40 cm in tissues of human body, such as softtissues, lungs and bones were made by using DOSXYZnrc. Nonhomogen phantom of human bodywas made by insert lungs or bones with thickness 10 cm in soft tissues at depth of 5 cm – 14 cm.It is obtained that the dose distribution of soft tissue and water phantom have samecharacteristic which both of them have maximum dose (D ) at depth of 1,5 cm. Inserting of lungswith a thickness of 10 cm in soft tissue results to the increasing of dose until 12,2 % and insertingof bones with the same thickness with lungs results to decreasing of dose until 10,3 %. The rangeof correction factor due to inserting lungs is 1,00–1,27 and for bone is 0,81–1,05.Keywords:Monte Carlo Simulation, PDD (Percentage Depth Dose), corrections factor